Advances in stem cell-based therapeutics for acute high-altitude illness: research progress and prospects - Dou, Bai-Tao; Li, Meng-Jiao; Li, Yan-Ling; Chen, Dan; Yang, Cheng-Wei; Fan, Fang-Yi; Yao, Hao (Frontiers in Physiology, 2025)
Acute high-altitude illness (AHAI), triggered by hypobaric hypoxia following rapid ascent to high elevations, induces complex pathophysiological responses that may be life-threatening. Recent advances in regenerative medicine have highlighted the therapeutic potential of stem cells in mitigating hypoxia-induced damage. Among them, Mesenchymal stem cells (MSCs), the most extensively investigated, exert therapeutic efficacy through immunomodulation, attenuation of oxidative stress, and enhancement of tissue repair mechanisms. Their paracrine signaling profile facilitates angiogenesis and stabilization of the hypoxic microenvironment. Neural stem cells (NSCs) exhibit robust proliferation and differentiation under hypoxic conditions, offering a novel avenue for the treatment of high-altitude cerebral pathology. Additionally, induced pluripotent stem cells (iPSCs), with their pluripotency and patient-specific derivation, present significant promise for personalized, cell-based interventions. Experimental studies demonstrate that these stem cell types modulate the hypoxic milieu via secretion of cytokines, remodeling of the immune microenvironment, and promotion of neovascularization. Nonetheless, several translational challenges persist, including suboptimal homing efficiency, potential immunogenicity, and uncertain long-term safety profiles in high-altitude settings. Future research should prioritize elucidation of stem cell behavior in hypobaric hypoxia, optimization of delivery systems, and establishment of standardized therapeutic protocols. Rigorous clinical validation through evidence-based approaches will be essential to substantiate safety and efficacy. With continued advances in stem cell biology and translational techniques, stem cell-based therapy is poised to emerge as a viable strategy for the prevention and management of AHAI, provided that its clinical deployment is underpinned by robust scientific evidence.